2013
DOI: 10.1371/journal.pone.0066530
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RNA-Dependent RNA Polymerase 1 and Isochorismate Synthase Gene Expression in Arabidopsis

Abstract: BackgroundRNA-dependent RNA polymerases (RDRs) function in anti-viral silencing in Arabidopsis thaliana and other plants. Salicylic acid (SA), an important defensive signal, increases RDR1 gene expression, suggesting that RDR1 contributes to SA-induced virus resistance. In Nicotiana attenuata RDR1 also regulates plant-insect interactions and is induced by another important signal, jasmonic acid (JA). Despite its importance in defense RDR1 regulation has not been investigated in detail.Methodology/Principal Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 64 publications
4
91
0
4
Order By: Relevance
“…Promoters of AGO Genes Contain Several ABREs, and Their Expression Levels Are Affected by Exogenous ABA Some reports indicated that ABA regulates several components of the sRNA pathway, such as AGO1 and its regulator miR168 as well as RdR1 (Li et al, 2012;Hunter et al, 2013;Alazem and Lin, 2015). We hypothesized that ABA-mediated resistance is achieved by positive regulation of the RNA-silencing pathway and that such regulation also may affect members of the AGO family because several of these proteins have antiviral properties (Carbonell and Carrington, 2015).…”
Section: Callose-deficient Plants Showed Reduced Bamv Levels Upon Trementioning
confidence: 99%
See 2 more Smart Citations
“…Promoters of AGO Genes Contain Several ABREs, and Their Expression Levels Are Affected by Exogenous ABA Some reports indicated that ABA regulates several components of the sRNA pathway, such as AGO1 and its regulator miR168 as well as RdR1 (Li et al, 2012;Hunter et al, 2013;Alazem and Lin, 2015). We hypothesized that ABA-mediated resistance is achieved by positive regulation of the RNA-silencing pathway and that such regulation also may affect members of the AGO family because several of these proteins have antiviral properties (Carbonell and Carrington, 2015).…”
Section: Callose-deficient Plants Showed Reduced Bamv Levels Upon Trementioning
confidence: 99%
“…While it is well established that salicylic acid (SA) controls plant resistance to virus infection via R gene resistance (Baebler et al, 2014), it also has been suggested that SA regulates a few genes in the RNA-silencing pathway (Alamillo et al, 2006;Hunter et al, 2013). In fact, the regulation of defense responses has been demonstrated to be a hormonetuned process in many cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recent findings demonstrated that Cauliflower mosaic virus (CaMV) P6 alters the expression and sub-cellular localization of NPR1 and inhibits the SAdependent defence responses (Love et al, 2012). Moreover, another recent report showed that SA-induced RDR1 expression is dependent on NPR1 (Hunter et al, 2013). Thus, although NPR1 does not seem to be involved in SA-mediated resistance, its role during compatible viral interactions cannot be ruled out at this stage.…”
Section: Rna Interference-mediated Resistancementioning
confidence: 99%
“…Interestingly; we observed that the expression of RDR1 was downregulated in mutant plants carrying a 17 amino acid deletion within the DELLA domain of GAI which are insensitive to GA treatment. Given that SA-induced RDR1 expression is dependent on NPR1 protein and is enhanced by H 2 O 2 (Hunter et al, 2013;Liao et al, 2013), it was proposed that DELLA could be attenuating RDR1 expression by its impact on SA signalling and ROS pathways (Rodriguez et al, 2014). Moreover, when viral accumulation was analysed in plants carrying a quadruple DELLA mutation, a reduced viral accumulation was observed in the quadruple DELLA mutants with respect to wild-type plants.…”
Section: Effects Of Tmv Coat Proteinmentioning
confidence: 99%